Revenge of the Right Brain. - Pink, Daniel H. (Public Management (00333611), 2007)
The article presents a discussion related to the function of man's left brain adapted from the book "A Whole New Mind: Moving from the Information Age to the Conceptual Age," by Daniel H. Pink.